Thermal radiation effects of ternary hybrid nanofluid flow in the activation energy: Numerical computational approach - Hakeem Ullah; Syed Arshad Abas; Mehreen Fiza; Aasim Ullah Jan; Ali Akgul; Magda Abd El-Rahman; Seham M. Al-Mekhlafi (Results in Engineering)
Significance: The remarkable thermal conductivity and heat transfer characteristics of nanofluids make them extremely valuable in thermal engineering and other areas. Due to their increased effectiveness, nanofluids are incredibly useful for improving the efficiency of cooling systems, heating processes, and thermal management applications. Rotating machinery and gas turbine rotators are some industrial applications of hybrid nanofluids as heat transport fluids. Purpose: This study introduces a novel investigation into heat transport phenomena of ternary hybrid, hybrid and nanofluid containing copper, silver and alumina nanoparticles within two stretchy rotating disks maintaining a constant distance. The analysis incorporates the effects of thermal radiation, heat source, joule heating, and Arrhenius activation energy into the equations to stabilize the new composition's flow and thermal properties. Methodology: After utilizing von Karman similarity transformations to renovate the principal equations into the set of nonlinear differential equation systems, the resulting equations were solved using the bvp4c numerical approach with the assistance of MATLAB software. Findings: Graphs are used to explain the results in three different kinds of flows: hybrid fluid (Cu+Al2O3/H2O), nanofluid (Cu/H2O), and ternary hybrid fluid (Cu+Al2O3+Ag/H2O). Additionally, the outcomes of the variable parameters are presented and briefly discussed for different flow profiles. There is encouraging evidence that the numerical code for this study is compatible with previously published work. The skin friction improves 5 % due to the higher values of magnetic and stretching parameter at lower disk. The rate of the heat transfer improved 28 % for ternary nanoparticles as compared to hybrid and single nanofluids. Sherwood's number exhibits both growing and decreasing behaviors for Schmidt and Reynolds’ numbers. All the involved factors enhances the temperature profile. The radiation parameter boost the Nusselt number for ternary hybrid nanofluid up to 6 % and 3.4 % at lower and upper disk as compare to nanofluid.